2016
DOI: 10.1007/s13280-016-0851-0
|View full text |Cite
|
Sign up to set email alerts
|

Environmental impacts of tobacco product waste: International and Australian policy responses

Abstract: The health risks of tobacco consumption are well established, but there is less awareness of the global environmental impacts of smoking. The by-products of the 6.3 trillion cigarettes smoked annually are filters (butts) that contain benzene, nicotine, cadmium, and dozens of other chemicals. It is estimated that between one-and twothirds of all filters are discarded on roads, pavements, and green spaces. Butt litter as an environmental and public health hazard is a relatively new field of study, but recent res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 32 publications
(48 reference statements)
0
21
0
3
Order By: Relevance
“…Indoors, the kitchen may be most affected by disposal of WPT waste. In the USA, trash bins are typically placed in the kitchen area, where smokers reported discarding their WPT White/grey/black 11 (19) Somewhat clear (1). It is smoky clear (1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indoors, the kitchen may be most affected by disposal of WPT waste. In the USA, trash bins are typically placed in the kitchen area, where smokers reported discarding their WPT White/grey/black 11 (19) Somewhat clear (1). It is smoky clear (1).…”
Section: Discussionmentioning
confidence: 99%
“…Global efforts to mitigate the adverse impact of postconsumption tobacco waste on the environment are on the rise, [1][2][3][4][5][6][7][8][9] prompted by concern over the 1.69 billion lbs (720 million kg) of cigarette butts that end up as toxic waste annually. 3 10 While regulatory efforts to reduce the environmental effects of tobacco product waste have been focused on cigarettes, 1-10 similar attention is warranted for other tobacco products.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Tobacco Atlas [30] reported that 5.7 trillion cigarettes were consumed worldwide in the year 2016 and that about 97% of the cigarette filters were made up of cellulose acetate filters, which is a modified natural polymer [31]. In Australia, every year, more than 20 billion cigarettes are consumed, and 7 billion are littered into the environment (Figure 1) [32]. Clean Up Australia [33] reported that CBs were the most common source of rubbish collected under the miscellaneous category, which represented 91.5%.…”
Section: Cigarette Buttsmentioning
confidence: 99%